A tale of dual-approach construct validation and reliability testing for a Zika infection awareness knowledge questionnaire - Chin Mun Wong; Mohd Rohaizat Hassan; Rozita Hod; Sharifa Ezat Wan Puteh; Sazaly Abu Bakar (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aims to validate the English version of a WHO-adapted questionnaire: Zika infection awareness/knowledge questionnaire using a unique dual-approach validation model. Design/methodology/approach - A cross-sectional pilot study of 30 adult respondents in Malaysia completed the self-administered questionnaire on knowledge and perception to Zika infection. Construct validity was assessed by exploratory factor analysis (EFA) of SPSS and Rasch partial credit. Reliability is tested using pKR20 and Cronbach's alpha. Findings - Knowledge construct was unidimensional, good model fit, easy to endorse and well discriminative. Five-rating Likert scale for perception domain was appropriate. Knowledge domain should be separated into 6 level of difficulties. Perception domain should remain as one construct. Knowledge domain was highly reliability (pKR20 = 0.96), perception domain was fairly reliable (Cronbach's alpha = 0.641). Respondent's ability to answer knowledge domain and perception domain were separated into 3 and 4 levels. Research limitations/implications - Small sample size may affect factor analysis. Practical implications - The questionnaire has good psychometric properties to measure the knowledge and perception of Zika infection among Malaysian community. Social implications - The questionnaire helped to gauge knowledge and perception of the general community in Malaysia to aid preparation of health education tool for Zika infection. Originality/value - This paper validated questionnaire with two biostatistical software programs in bidirectional approach - items difficulty and respondents' ability - is the first field test of WHO questionnaire among general population in Southeast Asia.